INTEGRASI MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS X SMAN 1 RANTAU SELATAN PEMBELAJARAN PENDIDIKAN PANCASILA - Anggraini, Meutia; Sari, Mila Nirmala (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This classroom action research aims to improve the learning outcomes of Class X students of SMAN 1 Rantau Selatan in Pancasila Education Learning with the material "Recognizing, Realizing, and Appreciating Identity Diversity" by integrating the Problem Based Learning (PBL) model with the Culturally Responsive Teaching (CRT) approach. This research follows the classroom action research design of Kemmis McTaggart and is carried out in three cycles, namely pre-cycle, cycle I, and cycle II, each consisting of 4 stages, such as planning, implementation, observation, and reflection. A total of 36 Class X-2 students became the subjects in this study. Data collection was carried out using observation and learning outcome tests. The results of the study showed that there was a significant increase in student learning outcomes. The average score of students increased from 63.3 in the precycle, to 78.6 in Cycle I, and 89.4 in Cycle II. The classical completion rate also showed a substantial increase, namely from 30.5% in the pre-cycle, 61.1% in Cycle I, to 91.6% in Cycle II. This study is expected to be a guideline in implementing a learning model that not only emphasizes critical problem solving through Problem Based Learning (PBL), but is also able to appreciate and accommodate the cultural diversity of students through the Culturally Responsive Teaching (CRT) approach.